2010
DOI: 10.1159/000314154
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transdermal Plasmid-Dimethylsulfoxide Delivery Technique for Treatment of Psoriasis

Abstract: Background: Psoriasis is a chronic and relapsing inflammatory skin disease associated with various immunologic abnormalities. Repeated subcutaneous injection of interleukin-4 (IL-4) has been established as an effective treatment to counteract psoriasis. Objective: We investigated whether gene therapy using IL-4 expression plasmid (pIL-4) via transdermal delivery was an alternative treatment for psoriasis. In our experiment, dimethylsulfoxide (DMSO) was used as a penetration enhancer. Methods: At first, the pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…DMSO has been shown to promote the permeation of, for example, antiviral agents, steroids and antibiotics 9 . We also confirmed that 10% DMSO was the optimal transdermal delivery formula for further examination in vivo 8 , 10 . These results provide a foundation for increasing the efficiency of gene transdermal penetration with DMSO.…”
Section: Introductionsupporting
confidence: 76%
“…DMSO has been shown to promote the permeation of, for example, antiviral agents, steroids and antibiotics 9 . We also confirmed that 10% DMSO was the optimal transdermal delivery formula for further examination in vivo 8 , 10 . These results provide a foundation for increasing the efficiency of gene transdermal penetration with DMSO.…”
Section: Introductionsupporting
confidence: 76%
“…In this issue Zhang et al [16] show that topical application of a plasmid encoding the IL-4 gene allows transdermal delivery of IL-4 and strongly improves skin inflammation in a model disease that closely mimicks psoriasis [17] . In this model, mice express the gene for the vascular endothelial growth factor in the basal keratinocytes.…”
Section: Requirements For Novel Psoriasis Therapiesmentioning
confidence: 99%
“…While under normal conditions, activation of Th cells results in Th1 or Th17 cells, priming of Th cells in the presence of either endogenous or exogenous IL-4 leads to a Th2 phenotype that is characterized by the production of IL-4 and strongly suppresses inflammation such as psoriasis in humans [14,22] , probably also multiple sclerosis and all experimental inflammatory diseases studied so far under in vivo conditions [15,16,18,19] . This is also the case in humans, as shown first in vitro and then in vivo [14,22] .…”
Section: Requirements For Novel Psoriasis Therapiesmentioning
confidence: 99%
“…Recent studies have demonstrated that skewing CD4 + T cell phenotype within psoriatic plaques to a Th2-type immune response can ameliorate disease [31], [32], [33]. Treatment of psoriasis patients with subcutaneous injections of IL-4 polarizes lesional T cell responses to a Th2-type and decreases psoriasis severity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of psoriasis patients with subcutaneous injections of IL-4 polarizes lesional T cell responses to a Th2-type and decreases psoriasis severity [31]. Similarly, transdermal delivery of IL-4 expression plasmid ameliorates disease in a mouse model of psoriasis [32], [33]. Thus, induction of a Th2 phenotype of skin infiltrating lymphocytes correlates with disease improvement.…”
Section: Introductionmentioning
confidence: 99%